2014
DOI: 10.2495/sdp-v9-n6-778-793
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of ISCST3, adms-urban and aermod for urban air quality management in a mega city of India

Abstract: Urban air quality has deteriorated in last few decades in the mega cities of both developed and developing countries. Many mathematical models have been widely used as prediction tool for urban air quality management in developed countries. However, applications of these models are limited in developing countries including India due to lack of suffi cient validation studies. In this paper, three state-of-the-art air quality models namely AERMOD, ADMS-Urban and ISCST3 have been used to predict the air quality a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Local weather data would produce more accurate results on the "micro" scale of this project. In addition, the choice of ISCST3 for this study over the recent EPA approved AERMOD was influenced by the fact that ISCST3 was found to perform better than AERMOD under stable winter conditions [35] and flat simple terrains [9] as has been the case in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Local weather data would produce more accurate results on the "micro" scale of this project. In addition, the choice of ISCST3 for this study over the recent EPA approved AERMOD was influenced by the fact that ISCST3 was found to perform better than AERMOD under stable winter conditions [35] and flat simple terrains [9] as has been the case in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Past studies have demonstrated the ability of dispersion models such as the American Meteorological Society/U.S. Environmental Protection Agency Regulatory Model (AERMOD) to simulate local emissions sources and ambient concentrations of gaseous and particulate pollutants in urban air pollution studies (Gibson et al, 2013;Gulia et al, 2014;Askariyeh et al, 2017;Katika and Karuchit, 2018;Salva et al, 2021) and to assess industrial source impacts (Seangkiatiyuth et al, 2011;Afzali et al, 2017;Tran et al, 2019;Hanma, 2021). As for simulating PM 2.5 in Bangkok, a review of source apportionment studies indicates that traffic emissions and biomass burning are the most important sectors (Wimolwattanapun et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…forecasts were the most accurate in terms of NOx and SO2 concentrations, while Caline4 overestimated NOx levels Gulia et al (2014). employed AERMOD, ADMS-Urban, and ISCST3 to estimate air quality at a particular intersection in Delhi, India.…”
mentioning
confidence: 99%